Synthesis of Sphingolipids Impacts Survival of Porphyromonas gingivalis and the Presentation of Surface Polysaccharides - Moye, Zachary D.; Valiuskyte, Kornelija; Dewhirst, Floyd E.; Nichols, Frank C.; Davey, Mary E. (Frontiers in Microbiology, 2016)
Bacteria alter the biophysical properties of their membrane lipids in response to environmental cues, such as shifts in pH or temperature. In essence, lipid composition determines membrane structure, which in turn influences many basic functions, such as transport, secretion, and signaling. Like other members of the phylum Bacteroidetes, the oral anaerobe Porphyromonas gingivalis possesses the ability to synthesize a variety of novel membrane lipids, including species of dihydroceramides that are distinct, yet similar in structure to sphingolipids produced by the human host. The role of dihydroceramides in the physiology and pathogenic potential of the human microbiota is only beginning to be explored; yet there is increasing data indicating that these lipids play a role in human diseases, such as periodontitis and multiple sclerosis. Here, we report on the identification of a gene (PG1780) in the chromosome of P. gingivalis strain W83 encoding a putative serine palmitoyltransferse, the enzyme that catalyzes the first step in sphingolipid biosynthesis. While we were able to detect dihydroceramides in whole lipid extracts of P. gingivalis cells as well as crude preparations of outer membrane vesicles, sphingolipids were absent in the PG1780 mutant strain. Moreover, we show that the synthesis of sphingolipids plays an essential role in the long-term survival of the organism as well as its resistance to oxidative stress. Further, a PG1780 mutant displayed much lower activity of cell-associated arginine and lysine gingipains, yet slightly higher activity in the corresponding culture supernates, which we hypothesize is due to altered membrane properties and anchoring of these proteases to the cell surface. In addition, we determined that sphingolipid production is critical to the presentation of surface polysaccharides, with the mutant strain displaying less K-antigen capsule and more anionic polysaccharide (APS). Overall, we have discovered that, in addition to their role in pathogenicity, the synthesis of sphingolipids is critical to the cellular homeostasis and persistence of this important dental pathogen.